CRISPR/Cas13a‐Powered Electrochemical Microfluidic Biosensor for Nucleic Acid Amplification‐Free miRNA Diagnostics. Issue 51 (30th October 2019) - Bruch, Richard; Baaske, Julia; Chatelle, Claire; Meirich, Mailin; Madlener, Sibylle; Weber, Wilfried; Dincer, Can; Urban, Gerald Anton
Abstract: Noncoding small RNAs, such as microRNAs, are becoming the biomarkers of choice for multiple diseases in clinical diagnostics. A dysregulation of these microRNAs can be associated with many different diseases, such as cancer, dementia, and cardiovascular conditions. The key for effective treatment is an accurate initial diagnosis at an early stage, improving the patient's survival chances. In this work, the first clustered regularly interspaced short palindromic repeats (CRISPR)/Cas13a‐powered microfluidic, integrated electrochemical biosensor for the on‐site detection of microRNAs is introduced. Through this unique combination, the quantification of the potential tumor markers microRNA miR‐19b and miR‐20a is realized without any nucleic acid amplification. With a readout time of 9 min and an overall process time of less than 4 h, a limit of detection of 10 pm is achieved, using a measuring volume of less than 0.6 µL. Furthermore, the feasibility of the biosensor platform to detect miR‐19b in serum samples of children, suffering from brain cancer, is demonstrated. The validation of the obtained results with a standard quantitative real‐time polymerase chain reaction method shows the ability of the electrochemical CRISPR‐powered system to be a low‐cost, easily scalable, and target amplification‐free tool for nucleic acid based diagnostics. Abstract : Without any target amplification, the first electrochemical microfluidic biosensor based on CRISPR/Cas13a enables the detection of the microRNA miR‐19b from serum samples from children suffering from brain cancer. The validation of the findings with a standard quantitative real‐time polymerase chain reaction demonstrates the suitability of the CRISPR‐powered biosensing system as a low‐cost, easily scalable, and target amplification‐free tool for on‐site nucleic acid diagnostics.